1992
DOI: 10.1055/s-0038-1648128
|View full text |Cite
|
Sign up to set email alerts
|

Behçet Syndrome Associated with Protein S Deficiency

Abstract: SummaryBeçget syndrome is a multisystem disorder characterized by ocular, mucocutaneous, articular, gastrointestinal and neurologic abnormalities. We report here an unusual case of Beçget syndrome, characterized by the importance of the thrombotic events(7 phlebitis of both legs and resection of two toes). Additional manifestations of the Beçget syndrome occurred only 10 years after the first thrombotic episode. The oldest daugther of the propositus and his brother suffered also from thrombophlebitis; this fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
2
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 6 publications
2
9
2
1
Order By: Relevance
“…Arterial thrombosis is infre-quent (2%), and occurs many years after onset of the disease. 3,6 In our study, the mean Protein S activity measured in the BD group was slightly lower than that of the control group, but no statistically significant differences could be demonstrated (p Ͼ 0.05). Compared with the means of the control group, the Protein C activities were not lower in BD.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Arterial thrombosis is infre-quent (2%), and occurs many years after onset of the disease. 3,6 In our study, the mean Protein S activity measured in the BD group was slightly lower than that of the control group, but no statistically significant differences could be demonstrated (p Ͼ 0.05). Compared with the means of the control group, the Protein C activities were not lower in BD.…”
Section: Discussioncontrasting
confidence: 54%
“…4 The basis of the thrombotic risk in BD is not understood. [4][5][6][7] Protein C and Protein S are major inhibitors of coagulation, and it is well known that the deficiency of these proteins causes thrombotic disorders. [6][7][8][9][10] In this study, normal healthy subjects and patients with BD were investigated in order to clarify whether Protein C and Protein S play any role in the hypercoagulable state which can be found in BD.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the involvement of other known or as yet unidentified procoagulant genetic defects might be expected in the remaining T + patients. In fact, protein C and protein S deficiency have previously been documented in cases of BD with extensive venous thrombosis [8,9].…”
Section: Discussionmentioning
confidence: 97%
“…Other alterations, such as deficiencies of protein C, protein S and antithrombin (AT), or the presence of antiphospholipid antibodies and factor V Leiden and prothrombin 20210A mutations, have been considered. Although some studies found an association between these abnormalities and thrombosis in Behçet's disease (Hull et al , 1984; Chafa et al , 1992; Guermazi et al , 1997; Mammo et al , 1997; Mader et al , 1999; Vayá et al , 2000), many other studies did not find any of these abnormalities to be associated with Behçet's disease (Lenk et al , 1998; Nalçaci & Pekçelen, 1998; Mader et al , 1999; Toydemir et al , 2000; Espinosa et al , 2002).…”
mentioning
confidence: 99%